Importancia de los pecaríes (Tayassu spp.) en la alimentación del jaguar (Panthera onca) - Aranda, Marcelo (Instituto de Ecología, A.C., 1994)
This paper presents the results of an analysis of 37 jaguar scats collected at the Calakmul Biosphere Reserve, in the State of Campeche. México, between 1989-1993. My results indicate that jaguars feed mainly on mammals (86%), but also on birds (10%), and reptiles (4%). Among the mammals, the most important prey species for the jaguar were collared peccary (42%), coati (18%), and armadillo (12%). Analyzing the feeding habits of the jaguar ín relation to prey availabiilty, I found the jaguar has a preference for the collared peccary, because this species was consumed more than expected by its availability. This situation was similar to other localities, so it is proposed that the peccaries are important prey species for the jaguar in almost all its geographical range. In this paper I propose that the robust constitution of the jaguar its very important for a strong predation on its primary prey, the peccaries.